Transformation In Urban Design - Sana Sati Abbas; Ahmed Tarq Tarq (Iraqi Journal of Architecture and Planning, 2009)
This research deals with the transformation in urban design , as a concept , which has beenfocused on by the Structuralism, and the Theorist and Designer of Late Post -Modern, for itsimportance as a Strategy in the Design Process.The concept had been studied in many Disciplines , such as Linguistics , Biology , andArchitecture.The Linguistics indicated that each systematic knowledge is composed from basic structurecalled the Deep Structure . This structure formed the basic rules of transformation, on whichthe system is stand , this structure is called by ( Chomesky) the Generating rules .Biology showed that the transformation which occurred on form , are external changes andconnected with the external form . While the substantial characteristics of the being are fixedduring the operation of development and growth.In Architecture , the Literature submitted the types of transformation , which were thetransformation in the elements and the transformation in the relationships . Also theysubmitted some transformation mechanisms , directly or indirectly . Also did the EthicsLiterature.The research aims to built a theoretical framework of tansformation, and determine the basicmechanisms used in Architecture and Urban Design.The research reached to five items determined the theoretical framework of the transformationwhich were , the aim of transformation , the transformation formulas , the types oftransformation , the transformation mechanisms, and the behavior of the systems during tleprocess of transformation.